2013
DOI: 10.1007/s12013-013-9713-6
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis and Vascular Remodeling in Chronic Airway Diseases

Abstract: Asthma and chronic obstructive pulmonary disease remain a global health problem, with increasing morbidity and mortality. Despite differences in the causal agents, both diseases exhibit various degrees of inflammatory changes, structural alterations of the airways leading to airflow limitation. The existence of transient disease phenotypes which overlap both diseases and which progressively decline the lung function has complicated the search for an effective therapy. Important characteristics of chronic airwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 105 publications
0
29
0
5
Order By: Relevance
“…Thereafter, a number of studies reported the involvement of specific growth factors, such as fibroblast growth factor (FGF), transforming growth factor (TGF) β1 and vascular endothelial growth factor (VEGF), during vascular remodelling in asthma and COPD [9][10][11][12]. Vascular remodelling, including thickening of the intimal and medial layers due to vascular smooth muscle (VSM) cell hypertrophy, is reported to progressively decline lung function [10,13] and vascular alterations in the pulmonary circulation may impair gas exchange in the alveolar compartments that result in pulmonary hypertension in some COPD patients [14].…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, a number of studies reported the involvement of specific growth factors, such as fibroblast growth factor (FGF), transforming growth factor (TGF) β1 and vascular endothelial growth factor (VEGF), during vascular remodelling in asthma and COPD [9][10][11][12]. Vascular remodelling, including thickening of the intimal and medial layers due to vascular smooth muscle (VSM) cell hypertrophy, is reported to progressively decline lung function [10,13] and vascular alterations in the pulmonary circulation may impair gas exchange in the alveolar compartments that result in pulmonary hypertension in some COPD patients [14].…”
Section: Introductionmentioning
confidence: 99%
“…В соответствии с со временными представлениями БА -это хроничес кое персистирующее воспалительное заболевание, ведущее к структурным изменениям и ремоделиро ванию дыхательных путей (ДП). В понятие «ремо делирование» включены следующие основные ком поненты: гипертрофия гладких мышц, гиперплазия бокаловидных клеток, субэпителиальный (субба зальный) фиброз и ангиогенез [1][2][3][4][5]; развитие брон хиальной гиперреактивности [6].…”
Section: дискуссииunclassified
“…В последние годы накапливается все больше данных об изменениях микроциркуляторного русла и ремоде лирование сосудов ДП у больных БА и ХОБЛ [46][47][48][49].…”
Section: дискуссииunclassified
See 1 more Smart Citation
“…Nowadays, it is well accepted that in addition to inflammation, airways remodelling is also a hallmark feature of asthma which has been implicated in regulating disease severity and control [2][3][4]. Airways remodelling refers to structural changes including loss of epithelial integrity, thickening of the subepithelial basement membrane caused by fibrosis, goblet cell metaplasia and submucosal gland enlargement, increased airway smooth muscle mass, increased airways vascularity and vascular remodelling [2][3][4]. Although the notion that airways remodelling is one of the key features of asthma is well established, the underlying mechanisms have not been fully clarified.…”
Section: Introductionmentioning
confidence: 99%